Novel and Simple LC-MS/MS Technique for the Simultaneous Quantitation of Metformin and Remogliflozin in Rat Plasma - Patel, Smit Jayantilal; Mehta, Hiralben; Shaik, Basheer Ahmmad; Khan, Nadeem (Indian Journal of Pharmaceutical Education and Research, 2026)
Background: Metformin and remogliflozin in fixed dose combination prescribe to control blood sugar and avoid long term complication associated with diabetes mellitus. Aim: The aim is to establish a straightforward and sensitive bioanalytical method as well as to validate LC/ MS-MS technique for the concurrent quantitative determination of metformin and remogliflozin in rat plasma. Materials and Methods: The analytical separation of analytes with contrast physicochemical properties was successfully performed with C18 column (BDS Hypersil, 150 x 4.6 mm, 3.5 micron) at 40oC on API 4000 Mass Spectrometer coupled with Nexera X2 HPLC. Mobile phase was composed of 10 mM ammonium acetate dissolved in Milli-Q water (pH 7) (25%) and acetonitrile (75%) (v/v) at 0.7 mL/min flow through isocratic elution. A 10 µL injection volume was utilized in a brief run time of 4 min. Results and Discussion: Developed LC-MS/MS technique has been validated as per ICH guidelines (ICH M10). The validation data showed a precise, accurate, selective method and recovery and stability falling within the acceptable limits. Conclusion: A meticulous, precise, and repeatable LC-MS/MS method employing liquid-liquid extraction has been developed for concurrent quantitation of metformin and remogliflozin in rat plasma. The benefits provided by this method in terms of plasma sample requirement for processing as well as improved both sensitivity and reproducibility. The established method is set to be employed for the simultaneous pharmacokinetic analysis of both analytes within a biological matrix.
Keywords: Acetonitrile; LC-MS/MS; ICH; Metformin; Remogliflozin; Simultaneous quantitation